(untitled) (Research, Society and Development, 2025)
During the COVID-19 pandemic, psychological suffering was intensified due to the social isolation measures. This study aims to investigate the effects of Integrative Community Therapy (ICT) in the online modality as a strategy to promote mental health during the pandemic in Brazil. To this end, an intervention study of mixed design, observational and longitudinal, with a pre-test at T0 and a post-test at T1, was conducted in the virtual environment of ICT circles. The sample comprised 65 participants who answered three forms at T0 and T1 containing questions from five psychological measurement scales. The Wilcoxon paired-sample test was used to compare the scores recorded at T0 and T1 for such scales. Furthermore, content analysis was used to organize and extract meaning from the qualitative data collected in an online thematic ICT circle. Quantitative analyses showed a higher level of psychological well-being at T1, specifically for three dimensions: positive relations with others (p-value < 0.05), environmental mastery (p-value = 0.021), and purpose in life (p-value = 0.048). In addition, content analysis revealed a predominance of reports on positive relations with others. Overall, the present study suggested that, during the pandemic, online ICT has contributed to maintaining essential elements associated with individuals’ mental health, such as close social relationships and meaning and purpose in life. Thus, given its low cost and accessibility, ICT emerges as a potential and innovative resource for promoting mental health in contexts of crisis and adversity.